MEMBANGUN LINGKUNGAN INTERNET SEHAT DI RUMAH TINGGAL DENGAN MENGGUNAKAN APLIKASI WEB FILTERING - Erika Ramadhani; Afif Wika Sadewa (Faculty of Industrial Technology Universitas Islam Indonesia, 2017)
Healthy internet is a human activity that access to the public network that the Internet is done in an orderly manner, good, and ethical in accordance with norms and rules that apply in the community. Healthy internet usage is also by not doing unlawful internet activity, one of them is accessing illegal content (adult website). Currently, the use of Internet technology in the home environment has been very developed, with the ease that given the use of the Internet will be increasing. The problem is how to create a healthy internet environment by not accessing adult website links so that it can be protected from the access of children under age in the neighborhood. To maintain the activities of Internet use at home, then made an application that serves to monitoring the access to the Internet, especially to block the activities of accessing illegal content. This application is made by implementing Squid by way of doing filtering to access web. The results of this study is an application that can be used to monitor the Internet access at home. So it can create a healthy internet environment at home.